PERAN ASEAN REGIONAL FORUM (ARF) DALAM MENCIPTAKAN KAWASAN BEBAS ILLEGAL, UNREPORTED, AND UNREGULATED (IUU) FISHING DI INDONESIA TAHUN 2015-2017 - Jihad Bahari Putri Harun; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study analyzes the role of ARF in creating IUU Fishing free area in Indonesia in 2015—2017. ARF as a security dialogue forum in Asia-Pacific helps Indonesia in creating an IUU Fishing free area by providing Indonesia with a forum for dialogue to raise the increasing number of IUU Fishing issues in IndonesiaThis study uses a pluralism perspective where policies can be from different actors and uses international organization theory. The method used is descriptive qualitative method with data collection using case studies literature and documentation studies from articles, journals, and sites on the Internet.This research shows that ARF as a security dialogue forum acts as a motivator and provides encouragement for ARF members to fight IUU fishing together. The second role of ARF is to become a communicator by providing information and recommendations to member countries regarding IUU Fishing, publishing meeting results, co-chair statements, and chairman statements. The third role of ARF is to become an intermediary by holding meetings to discuss and equalize perceptions about IUU Fishing and to issue a joint statement indicating that IUU Fishing is an issue that must be eliminated and make the Asia-Pacific region a free area of IUU Fishing. Keywords: Role, IUU Fishing, ARF, Security Dialogue.